La práctica vocal para el desarrollo rítmico - auditivo de los adolescentes y jóvenes de la modalidad Miespacio Juvenil - Loja perteneciente al MIES (Ministerio de Inclusión Económico y Social) en el periodo 2013-2014 - Ramon Silva, Joao Paul (2015)
This research emphasizes provide the rhythmic and auditory development of adolescents and youth in the MIESpacio mode - Youth Loja, through the creation of a vocal ensemble that was made with members of this program being the contribution of the General Purpose this research work. The methodology used was action research it consisted in providing solutions to a problem of reality with a population of 12 boys, with their respective authority of the above method, of which a first sample information was obtained on their rhythmic and auditory capabilities; learning through field observation sheet, the process was developed through two learning phases, the first rhythmic, auditory exercises musical values and customs which were to the pair of music theory interactively with member and the second with the vocal ensemble, where he proceeded to apply the exercises and theory given above. The results obtained were excellent in improvements in their rhythm and hearing. The research was part of the research line 2 Musical Career Education, called Music as Potenciadora of learning in the educational-training process of human beings. Through interviews and surveys, it was possible to describe events using scientific, statistical and analytical methods - Synthetic. Finally it was concluded that experimentation between music and rhythmic development - ear is all-important for a development either artistic as daily life in order to provide a consistent manner an end result, but it is an activity that is currently zero, so which it is recommended to use this resource to enhance the expression.